2008
DOI: 10.1007/s10649-008-9139-z
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive styles, dynamic geometry and measurement performance

Abstract: This paper reports the outcomes of an empirical study undertaken to investigate the effect of students' cognitive styles on achievement in measurement tasks in a dynamic geometry learning environment, and to explore the ability of dynamic geometry learning in accommodating different cognitive styles and enhancing students' learning. A total of 49 6th grade students were tested using the VICS and the extended CSA-WA tests (Peterson, Verbal imagery cognitive styles and extended cognitive style analysis-wholistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 27 publications
0
10
0
4
Order By: Relevance
“…The aggregate scores are used to calculate ratios that group participants into cognitive styles. Thus test reliability and integrity is maintained across studies by testing each child individually using the same computer programme (see Dorum and Garland 2011;Pitta-Pantazi and Christou 2008;Yuan and Liu 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aggregate scores are used to calculate ratios that group participants into cognitive styles. Thus test reliability and integrity is maintained across studies by testing each child individually using the same computer programme (see Dorum and Garland 2011;Pitta-Pantazi and Christou 2008;Yuan and Liu 2011).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Woolner (2004) found an early secondary class taught verbally performed better in two mathematics topics than a matched class taught using a visual style. Similarly, Pitta-Pantazi and Christou (2008) found students classified with a verbal style, as measured by the Verbal-Imagery cognitive style, benefited most from using dynamic geometry software when learning the area of triangles and parallelograms for the first time. By contrast, other authors have found no differences between an imagery or verbal style in mathematics performance (e.g.…”
mentioning
confidence: 88%
“…Beberapa penelitian tentang gaya kognitif dalam pembelajaran matematika telah dilakukan. Penelitian yang dilakukan Pittapantazi dan Christou menunjukkan bahwa ada perbedaan performa antara calon guru yang bergaya kognitif Verbalisers-Imagers dan calon guru yang bergaya kognitif Wholistic-Analytics dalam menyelesaikan tugas pengukuran (Pitta-pantazi & Christou, 2009). Perbedaan ini terjadi pada calon guru yang berkemampuan rendah sedangkan calon guru yang berkemampuan tinggi memecahkan masalah dengan cara yang sama.…”
Section: Representasiunclassified
“…These factors should be taken into account in the use of modern technologies in the teaching and learning process. This is investigated, for example, in studies done by Pitta and Christou (2008) who focused on the influence of dynamic geometry on the cognitive styles of students. Davis and Simmt (2003) verified that learning in a classroom represents a complex reality and the implementation of technologies into the learning process could bring even more complexities.…”
Section: Ict In Teaching Mathematics and Languagesmentioning
confidence: 99%